A Fishy Story Promoting a False Dichotomy to Policy-Makers: It Is Not Freshwater vs. Marine Aquaculture. Issue 4 (13th September 2022) - Costa-Pierce, Barry Antonio; Bockus, Abigail B.; Buck, Bela H.; van den Burg, Sander W. K.; Chopin, Thierry; Ferreira, Joao G.; Goseberg, Nils; Heasman, Kevin G.; Johansen, Johan; Shumway, Sandra E.; Sims, Neil A.; Tacon, Albert G. J.
Abstract: A recent publication by Belton et al. raises points for policy-makers and scientists to consider with respect to the future of aquaculture making recommendations on policies and investments in systems and areas of the world where aquaculture can contribute most. Belton et al. take an 'us versus them' approach separating aquaculture by economics, livelihood choices, and water salinity. They conclude "that marine finfish aquaculture in offshore environments will confront economic, biophysical, and technological limitations that hinder its growth and prevent it from contributing significantly to global food and nutrition security." They argue that land-based freshwater aquaculture is a more favorable production strategy than ocean/marine aquaculture; they disagree with government and non-governmental organizations spatial planning efforts that add new aquaculture to existing ocean uses; they advocate for open commons for wild fisheries as opposed to aquaculture; and they oppose 'open ocean' aquaculture and other types of industrial, capital-intensive, 'carnivorous' fish aquaculture. They discredit marine aquaculture rather than explain how all aquaculture sectors are significantly more efficient and sustainable for the future of food than nearly all land-based animal protein alternatives. As an interdisciplinary group of scientists who work in marine aquaculture, we disagree with both the biased analyses and the advocacy presented by Belton et al. Marine aquaculture is growing and is already making a significant contribution to economies and peoples worldwide. None of the concerns Belton et al. raise are new, but their stark statement that farming fish in the sea cannot 'nourish the world' misses the mark, and policy-makers would be wrong to follow their misinformed recommendations.